PERAN PERLINDUNGAN INVESTOR SEBAGAI MODERASI HUBUNGAN TANGGUNG JAWAB SOSIAL DAN EFISIENSI INVESTASI (Studi Empiris pada Perusahaan Sub Sektor Pakaian Jadi dan Tekstil di Indonesia yang Terdaftar di Index Bloomberg pada Tahun 2017-2021) - Widianti, Bethari Ayu; Ghozali, Imam (Diponegoro Journal of Accounting, 2024)
The textile industry is a manufacturing sector that has a sizeable contribution to the national economy. According to the Central Bureau of Statistics, in the first quarter of 2023 it was recorded as contributing 380.4 tons of exports. However, along with the increasing demand for textile products, this industry creates many negative social and ecological impacts. Therefore, many companies carry out social responsibility activities as a form of accountability for the impacts that have been caused. This study aims to examine how the influence of investor protection as a moderator between the relationship of social responsibility to investment efficiency. This research uses corporate social responsibility as the independent variable and investment efficiency variable as the dependent variable and investor protection variable as the moderating variable. In addition, this study also uses Tobin's Q, leverage, cash, firm age, and loss variables as control variables. Using a sample of 9 apparel and textile companies in Indonesia listed on the Bloomberg Index for 2017-2022, this study uses a panel data regression method with the Common Effect Model (CEM) estimator.The results of this study indicate the influence of social responsibility on investment efficiency. Investor protection has no significant effect in moderating the relationship between social responsibility and investment efficiency. Therefore, it can be concluded that investor protection is a moderating homologyser or a variable that is considered to have the potential to become a moderating variable.